Ultrathin Sub-5-nm Hf₁₋ₓZrₓO₂ for a Stacked Gate-all-Around Nanowire Ferroelectric FET With Internal Metal Gate - Shen-Yang Lee (IEEE, 2021)
This study investigates a device’s ability to boost its on-state current and subthreshold behavior using a ferroelectric field-effect transistor (FeFET) with an ultrathin sub-5-nm Hf1-xZrxO2 (HZO). A conventional field-effect transistor (FET) with pure hafnium (HfO2) is used as a control measure and the impact of an internal metal gate (IMG) is also discussed. The study was conducted by using a sub-5-nm HZO and seed layer to fabricate a gate-all-around (GAA) nanowire (NW); a FeFET with a metal-ferroelectric–metal-insulator-semiconductor (MFMIS) structure; and a double layer (DL) of the channel. The channel size used in the experiment was approximately $9.6×16$ nm2 and the total thickness of the gate stack was 9.2 nm. This thickness is 50.5% less than our previous experiment. The FeFET exhibits a considerably high ${I}_{on}$ – ${I}_{off}$ ratio exceeding 107. The IMG serves as a potential equalizer and the ferroelectric material is arranged in a more symmetrical electric field. This results in a lower subthreshold (sub- ${V}_{TH}$ ) swing ( $S.S._{min}=$ 49.3mV/decade) with a wide range ( $10^{3}$ ) of drain currentcompared to that without an IMG. The findings indicate that a high-performance GAA FET can be achieved by combining a DL channel, GAA NW, ferroelectric material, and an IMG.